2020
DOI: 10.30994/sjik.v9i1.284
|View full text |Cite
|
Sign up to set email alerts
|

Guided Imagery To Reduce Insomnia in Elderly

Abstract: One of the actions that can be given to improve sleep quality in elderly with insomnia is Guided Imagery Therapy. The long term goal of research was to determine the effect of Guided Imagery Therapy against Insomnia In Kota Wilayah Utara Public Health Center Kediri. The design in this research was Pre Experiment Design of Pre-Post Test Design. The population were all elderly who have insomnia with sample number that is equal to 36 respondents, data retrieval by using purposive sampling technique. The collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…From the results of the analysis of sleep quality scores with the PSQI questionnaire before and after the intervention, it was found that the p-value was 0.000 (p-value < 0.05), which means that the therapy provided was influential in helping to improve the sleep quality of the respondents-involved in the research. Data that supports that guided imagery therapy affects sleep quality improvement were found in a study by Mahanani (2020), showing guided imagery helps elderly patients with insomnia. In his research, Mahanani found that 6 of 26 research respondents felt their insomnia reduced after guided imagery therapy.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…From the results of the analysis of sleep quality scores with the PSQI questionnaire before and after the intervention, it was found that the p-value was 0.000 (p-value < 0.05), which means that the therapy provided was influential in helping to improve the sleep quality of the respondents-involved in the research. Data that supports that guided imagery therapy affects sleep quality improvement were found in a study by Mahanani (2020), showing guided imagery helps elderly patients with insomnia. In his research, Mahanani found that 6 of 26 research respondents felt their insomnia reduced after guided imagery therapy.…”
Section: Resultsmentioning
confidence: 76%
“…In addition, this therapy may also be able to help the elderly to regain a source of confidence and a sense of independence because of their direct involvement in the healing process. In a study conducted by Mahanani (2020), it was found that guided Imagery can help reduce insomnia, where 21 of a total of 39 research respondents experienced a decrease in insomnia disorder after giving an intervention in the form of guided imagery relaxation therapy. Onieva-Zafra (2019), in a study, suggested that guided Imagery is a beneficial alternative therapy for patients where this relaxation therapy helps patients reduce patient complaints such as anxiety and sleep disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil penelitian ini juga didukung dengan penelitian yang dilakukan oleh Idris & Astarani (2019) yang menunjukkan bahwa mayoritas tingkat insomnia pada lansia berada pada kategori ringan (35,7%) dan kategori sedang (42,9%) dari jumlah responden sebanyak 14 responden. Selain, penelitian yang dilakukan oleh Mahanani (2020) juga menunjukkan bahwa mayoritas responden lansia mengalami insomnia (80,55%). Penelitian Brewster et al (2018) juga menunjukkan bahwa lebih dari 50% lansia menunjukkan gejala dari insomnia.…”
Section: Pembahasanunclassified
“…Therefore, prevention and nursing therapy are needed to avoid the emergence of health problems caused by insomnia. One of these prevention efforts is to use guided imagery therapy (Mahanani, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Guided imagery therapy for the elderly is needed to provide a sense of calm, relaxation, and relaxation (Krau, 2020) (Mahanani, 2020). Guided imagery or visualization as a therapy that focuses on depicting calming objects, sights, events, or things can replace negative feelings with feelings of relaxation or relaxation (Haslina et al, 2021).…”
Section: Introductionmentioning
confidence: 99%